The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Mackenzie, Bev; Celliers, Louis; Assad, Luiz Paulo de Freitas; Heymans, Johanna J.; Rome, Nicholas; Thomas, Julie; Anderson, Clarissa; Behrens, James; Calverley, Mark; Desai, Kruti; DiGiacomo, Paul M.; Djavidnia, Samy; et al. (Frontiers in Marine Science, 2019)
The importance of stakeholder engagement in ocean observation and in particular the realization of economic and societal benefits is discussed, introducing a number of overarching principles such as the convergence on common goals, effective communication, co-production of information and knowledge and the need for innovation. A series of case studies examine the role of coordinating frameworks such as the US’s Interagency Ocean Observing System (IOOS®), and the European Ocean Observing System (EOOS), public-private partnerships such as Project Azul and the Coastal Data Information Program (CDIP) and finally the role of the “third” or voluntary sector. The paper explores the value that stakeholder engagement can bring as well as making recommendations for the future.